Magnetite nanoparticles induced adaptive mechanisms counteract cell death in human pulmonary fibroblasts. Issue 7 (October 2015) - Radu, Mihaela; Dinu, Diana; Sima, Cornelia; Burlacu, Radu; Hermenean, Anca; Ardelean, Aurel; Dinischiotu, Anca
Graphical abstract